Useful- Capable- Successful: The Representation of Emancipation and Assimilation in the Historical Narratives of the Prague Jewish Community - Schreiberová, Zuzana (Dějiny – teorie – kritika, 2015)
The submitted essay deals with the topic of creating a group identity of Prague Jewish communities based on the fact how these Jewish communities perceive Czech Jewish history and their role in it. The key concept of this work is Hayden White´s Narrative Theory and also authors dealing with memory, as Maurice Halbwachs or Pierre Nora. The main sources of this work are numerous articles following up historical topics, published in four magazines issued by Jewish communities (Roš Chodeš, Obecní noviny, Maskil, Židovské listy). The aim of the work is to discover if the narrative form of Czech Jewish history is influenced by the fact, that the given community considers itself reform or orthodox, or if we should include any other factors. One of the factors may be politics of identities and internal conflicts.